Factors influencing student achievement in DEP30013 communication system fundamentals / Azimah Jusoh @ Alias, Anis Salwani Abu Bakar and Nor Hamiza Ghazali - Jusoh @ Alias, Azimah; Abu Bakar, Anis Salwani; Ghazali, Nor Hamiza
The purpose of this research is to identify the factors that influence students’ achievement in DEP30013 Communication System Fundamentals course at the Department of Electrical Engineering, Sultan Haji Ahmad Shah Polytechnic (POLISAS). These factors are student interest, student attitude, student learning methods, polytechnic environment and lecturer teaching. The study population is 120 people comprising third semester students who have taken this course in June Session 2019. The study sample of 35 people was taken at random. The instrument used was a questionnaire. The data collected were analyzed descriptively using Statistical Package for Social Science (SPSS) version 26.0. From the five factors studied, it was found that the mean for the lecturer's teaching factor was the highest at 4.51. Followed by attitude factor (4.39), polytechnic environmental factor (4.36), interest factor (4.27) and student learning method factor (4.25). Based on the research findings, the study found that the teaching factors of lecturers most influence student achievement.